Diffusion of implanted nitrogen in germanium. Issue 1 (10th December 2012) - Skarlatos, Dimitrios; Barozzi, Mario; Bersani, Massimo; Vouroutzis, Nikos Z.; Ioannou‐Sougleridis, Vassilios
Abstract In the present work diffusion of implanted nitrogen in germanium is studied as a function of implantation energy and post‐implantation annealing temperature. Implantations have been performed at a constant dose and energies leading to the amorphization of the substrate. Nitrogen diffusion in Ge is anomalous (not obeying the 2nd Fick's law) towards the substrate surface on which an Al2O3 layer has been deposited before annealing for protection. There is evidence that N diffusion in Ge is interstitial‐assisted and takes place in the presence of Ge interstitials gradients between the Al2O3/Ge and the former amorphous/crystalline (a/c) interface of the substrate during annealing. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)